ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RGEC PADA BANK UMUM SWASTA NASIONAL PERIODE 2020-2021 - Adenia Deffa Zhafira; Lutfi Ardhani (Jurnal Ilmiah Akuntansi Peradaban, 2023)
This study aims to assess the bank health level of national private public banks In 2020-2021 using the RGEC method, which is viewed from the factors of Risk Profile, Good Corporate Governance, Earnings, and Capital. The financial ratios used in assessing the health level of bank include risk profile using 2 ratios, namely NPL and LDR, GCG factor using the results of the self-assessment, Earnings using 4 ratios, namely ROA, ROE, NIM, BOPO. Capital uses the CAR Ratio. The results of this study indicate that National Private Public Banks Health Level in 2020 received the predicate â€œFairly Healthyâ€ and in 2021 received the predicate â€œHealthyâ€ Keywords : Bank Health Level, RGEC, National Private Public Banks